Determinants of Exclusive Breastfeeding of Infants under Six Months among Cambodian Mothers - Sopheak Um; Ying Zhen Charissa Chan; Bunkea Tol; Heng Sopheab (Hindawi Limited, 2020)
Introduction. Practicing exclusive breastfeeding (EBF) in an infant's first six months of life is recommended by the World Health Organization because of its proven effectiveness as a method to support the infant's short- and long-term physical and cognitive development. However, many countries, including Cambodia, face contextually driven challenges in meeting this optimum standard of breastfeeding. The recent declining EBF rate in Cambodia is a concerning indicator of the impact of these challenges. Methods. We used existing data from the 2014 Cambodian Demographic and Health Survey (CDHS) to analyze 717 Cambodian mother-infant pairs. CDHS 2014 used a two-stage stratified cluster sampling approach to select samples. A multivariable logistic regression analysis was used to assess determinants of EBF, taking into account the sampling weight in the analysis. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) were calculated, and significance level was considered at p value < 0.05. Results. Our findings indicate that among mothers with infants under six months, EBF was more likely if they resided rurally (AOR=2.28; 95% CI 1.23-4.23) and if they delivered at a public hospital (AOR=2.64; 95% CI 1.28-5.47). On the other hand, mothers of middle wealth index practiced EBF less than mothers of low wealth index (AOR=0.58; 95% CI 0.34-0.99). And as expected, our analysis confirmed that the older the infants grew, the less likely they were to be exclusively breastfed than those younger than one month old (2-3 months: AOR=0.49; 95% CI 0.26-0.92; 4-5 months: AOR=0.25; 95% CI 0.15-0.43). Conclusion. The findings emphasize the need to address these determinants adequately by appropriate interventions to halt the declining trend of EBF practice. We recommend a multifaceted approach to improve EBF rates in Cambodia. Advocacy around EBF at public hospitals should continue, and private hospital staff should receive training to provide EBF counselling and support to mothers.